2013
DOI: 10.4236/ojst.2013.38070
|View full text |Cite
|
Sign up to set email alerts
|

Pathological fractures of the mandible: A report of ten cases and a review of the literature

Abstract: Introduction: Pathological fractures of the mandible are rare. They account for approximately 2% of all mandibular fractures. The main purpose of the study is to report our experience concerning this condition and to analyse data and review the literature available. Material and methods: This study reviewed retrospectively the records of patients who presented to the department of Plastic and Maxillofacial surgery between 2000 and 2008 with a pathological fracture of the mandible. The collected data included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Coletti and Orb also reported that in the few cases in which sufficient bone was left to buttress the fracture, traditional fracture reduction with rigid fixation was employed. As a result, if the potential for bone healing exists, traditional rigid fixation rather than bone resection is recommended [ 1 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coletti and Orb also reported that in the few cases in which sufficient bone was left to buttress the fracture, traditional fracture reduction with rigid fixation was employed. As a result, if the potential for bone healing exists, traditional rigid fixation rather than bone resection is recommended [ 1 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%